Analisis Konsumsi Dalam Memengaruhi Kesejahteraan di Indonesia Selama Pandemi - Sari, Erin Novita; Fisabilillah, Ladi Wajuba Perdini (Universitas Negeri Surabaya, 2024)
This study aims to analyze the effect of consumption on welfare in Indonesia from 2020-2021. Data is sourced from BPS publications on its official website. The sampling technique used is purposive sampling with the criteria set, namely provinces in Indonesia whose HDI and consumption data have been published by BPS. The research method used is Panel Data Regression with the estimation model chosen is the Fixed Effect Model (FEM) with White Robust Standard Error to overcome heteroscedasticity problems. The results show that consumption has a significant effect on welfare in Indonesia.